Pengaruh Kompetensi Pemimpin, Disiplin Kerja Dan Iklim Organisasi Terhadap Produktifitas Pegawai - Arif Marjuki; M. Ifran Sanni; Wahyu Hidayat (UNIVERSITAS RAHARJA, 2018)
This study aimed to determine the effect of leadership competencies, work discipline and organizational climate partially or jointly against employee productivity. This study uses quantitative methods to survey techniques. Data collection instrument used was a questionnaire enclosed with Likert scale. This research uses a random sample of the number of respondents is 72 employees. Data obtained from this study will be analyzed using statistical methods with SPSS version 19 for Windows. The results of this study indicate that There is a positive and significant influence between the competence leader (X1) on the productivity of employees (Y) with a correlation coefficient of determination of 0.312 with a simple regression equation = 16,095 + 0,426X1. There is a positive and significant effect of labor discipline (X2) to the satisfaction of productivity of employees (Y) with a correlation coefficient of determination of 0.373 with a simple regression equation = 23.561 + 0,463X2. There is a positive and significant influence between organizational climate (X3) on productivity of employees (Y) with a correlation coefficient of determination of 0.323 with a simple regression equation = 11.292 + 0,687X3. There is a positive and significant influence competence leader (X1), work discipline (X2) and organizational climate (X3) together on productivity (Y), multiple correlation coefficient of determination obtained 0,929 with multiple regression equation = 6.312 + 0,152X1 + 0.257X2+0,306X3. This research is expected to be useful for companies in particular to increase employee productivity maximally. Researchers suggest that corporate management, always improve the competence of leaders, work discipline and organizational climate so that employee productivity increases in the future.